2021
DOI: 10.3390/jcm10163600
|View full text |Cite
|
Sign up to set email alerts
|

Zygomatic Implants Placed in Immediate Function through Extra-Maxillary Surgical Technique and 45 to 60 Degrees Angulated Abutments for Full-Arch Rehabilitation of Extremely Atrophic Maxillae: Short-Term Outcome of a Retrospective Cohort

Abstract: The use of new devices for the rehabilitation of the severely atrophic maxillae needs validation. We aimed to report the short-term outcome of severely atrophic jaws rehabilitated with zygomatic implants with no implant head angulation placed extramaxillary in conjunction with standard implants. Forty-four patients were consecutively included with 77 zygomatic implants (31 abutments of 45 degrees and 46 abutments of 60 degrees) and 115 standard implants. Outcome measures were prosthetic survival, implant/abutm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In contrast to the results of this study, an increase in stress was observed in the groups using a 30-degree multi-unit abutment. [30] Planning an implant-supported prosthetic restoration is an important factor affecting the amount of stress on implants. When we look at the literature on this subject, the study conducted by Yu et al comparing single-piece prostheses with multi-piece prostheses demonstrates that in single-piece prostheses where cantilevers are not used, the force distribution is more homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the results of this study, an increase in stress was observed in the groups using a 30-degree multi-unit abutment. [30] Planning an implant-supported prosthetic restoration is an important factor affecting the amount of stress on implants. When we look at the literature on this subject, the study conducted by Yu et al comparing single-piece prostheses with multi-piece prostheses demonstrates that in single-piece prostheses where cantilevers are not used, the force distribution is more homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…7 In clinical studies, cumulative survival rates, ranging from 95.2% to 98.6%, were achieved with a follow-up of 2-12 years. [10][11][12][13] Despite the advantages and success rates, complications associated with zygomatic implant treatment such as sinusitis, soft tissue infection, paresthesia, and orbital perforations can occur. However, the incidence of prosthetic complications is very low (4.9%) regardless of the type of prosthetic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The implant technique involves bypassing the atrophic alveolar bone and using the highly dense bone of the zygomatic complex as the fixation unit for longer implants (30–52.5 mm long) 7 . Indications for zygomatic implants may include rehabilitation of atrophic maxilla, 8 treatment of patients with ectodermal dysplasia, 9 and post‐surgical maxillary reconstruction in patients with oral cancer 10 . The success rate of treatment increases with the use of zygomatic implants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations